Contextual and Individual-Level Determinants of Physicians’ Acceptance of Electronic Medical Records: A Systematic Review Across Diverse Health Systems - Satria, Alfan; Imran, Abdul Waris; Yacobus, Danny Jaya; Suryana, Hari; Yuliaty, Farida (Jurnal Locus Penelitian dan Pengabdian, 2025)
The application of Electronic Medical Records (Rekam Medis Elektronik, RME) has great potential to improve the quality of health services, but the rate of acceptance by physicians still varies across different contexts. This study aims to identify individual and contextual factors that influence the acceptance of RME by physicians based on recent empirical studies. A systematic review was conducted through an article selection process using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Articles were systematically searched using the keywords: "electronic medical record" AND "physician" AND "acceptance" AND "factor" in the PubMed and ScienceDirect databases. The review was guided by the PICO framework. For this study, P: Physicians, I: Factors influencing acceptance of RME, C: Comparisons between regions, health systems, or types of RME, O: Acceptance of RME. Eight studies met the inclusion criteria, and a narrative synthesis was conducted. The most dominant individual factors included attitudes, perceptions of ease of use, and digital literacy. Key contextual factors were organizational support, technology infrastructure, and leadership engagement. Variations in acceptance patterns were observed between high- and middle-income countries. The acceptance of RME by physicians’ results from a complex interaction between individual-level and contextual determinants. Therefore, implementation strategies for RME should emphasize training, organizational support, and local characteristics to promote sustainable adoption and utilization of EMRs.